SMART URBANIZATION AND ECONOMIC TRANSFORMATION OF THE CITIES OF UZBEKISTAN - Dilshod Khaydarov (The Conference Hub, 2025)
Smart urbanization is becoming an essential pillar of national development strategies worldwide. This article examines how cities can be transformed into sustainable economic engines, focusing on Uzbekistan's evolving urban landscape. Through qualitative analysis and case comparisons, it identifies factors like innovation, infrastructure, and governance that influence the efficiency of urban economies. The study concludes with recommendations for sustainable and inclusive urban growth.
Keywords: smart cities, sustainable development, urban planning, innovation clusters, infrastructure, migration, environment, Uzbekistan, economic zones